2-(4-Methoxyphenyl)-1-pentyl-4,5-diphenyl-1H-imidazole - Antar A. Abdelhamid (Acta Crystallographica Section E, 2013)
The title compound, C27H28N2O, is a lophine (2,4,5-triphenyl-1H-imidazole) derivative with an n-pentyl chain on the amine N atom and a 4-methoxy substituent on the benzene ring. The two phenyl and methoxybenzene rings are inclined to the imidazole ring at angles of 25.32 (7), 76.79 (5) and 35.42 (7)°, respectively, while the methoxy substituent lies close to the plane of its benzene ring, with a maximum deviation of 0.126 (3) Å for the methoxy C atom. In the crystal, inversion dimers linked by pairs of C—H...O hydrogen bonds generate R22(22) loops. These dimers are stacked along the a-axis direction.